When language comprehension reflects production constraints: Resolving ambiguities with the help of past experience - MacDonald, Maryellen C. (Mem Cognit, 2009)
A key assumption in language comprehension is that biases in behavioral data, such as the tendency to interpret John said that Mary left yesterday to mean that yesterday modifies the syntactically local verb left, not the distant verb said, reflect inherent biases in the language comprehension system. In the present article, an alternative production–distribution–comprehension (PDC) account is pursued; this account states that comprehension biases emerge from different interpretation frequencies in the language, which themselves emerge from pressures on the language production system to produce some structures more than others. In two corpus analyses and two self-paced reading experiments, we investigated these claims for verb modification ambiguities, for which phrase length is hypothesized to shape production. The results support claims that tendencies to produce short phrases before long ones create distributional regularities for modification ambiguities in the language and that learning over these regularities shapes comprehenders’ interpretations of modification ambiguities. Implications for the PDC and other accounts are discussed.